PENGARUH KEPEDULIAN LINGKUNGAN DAN PENGETAHUAN LINGKUNGAN TERHADAP PERILAKU PRO LINGKUNGAN YANG DIMEDIASI OLEH SIKAP - Muhammad Affan Ardana; Aflit Nuryulia Praswati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to analyze the influence of environmental concern and environmental knowledge on pro-environmental behavior mediated by attitudes. This research method is quantitative. This study used primary data. Data collection methods used with the dissemination of questionnaires. The questionnaire was created using Likert scale format. The population in this study is the people of SoloRaya. The sampling technique in this study is non probability sampling. Through this Maholtra calculation, the minimum number of samples needed was obtained as many as 140 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. Based on the results and discussion, it was obtained that environmental concern has a positive and significant effect on pro-environmental behavior. Environmental knowledge has a positive and significant effect on pro-environmental behavior. Environmental concern has a positive and significant effect on attitudes. Environmental knowledge has a positive and significant effect on attitudes. Attitudes have a positive and significant effect on pro-environmental behavior. Attitudes mediate the influence of environmental concern on pro-environmental behavior, partially. Media attitudes influence environmental knowledge on pro-environmental behavior.